Sales Growth, Free Cash Flow, and Capital Structure in Indonesian LQ45 Stock Returns - Yurike Okvia; Fitri Mareta; Eksa Ridwansyah (LPPM STIE KRAKATAU, 2026)
This study examines the relationships between sales growth, free cash flow, capital structure, and stock returns among companies consistently included in the LQ45 index of the Indonesia Stock Exchange during 2021–2025. The study uses secondary financial statement and stock price data. Purposive sampling selected 23 firms with 115 firm-year observations, while the final pooled multiple regression used 110 observations after outlier removal. Stock return is measured through capital gain/loss, free cash flow through operating cash flow minus capital expenditure scaled by total assets, and capital structure through the Debt-to-Equity ratio (D/E). Sales growth and free cash flow have positive and significant associations with stock returns (B=0.385, p=0.001; B=0.827, p=0.011), whereas capital structure has a negative but insignificant association (B=−0.001, p=0.973). The model is jointly significant (F=7.924, p<0.001) and explains 18.3% of stock return variation (adjusted R²=16.0%). Investors appear to respond more strongly to revenue growth and operating cash availability than leverage levels. The study uses pooled firm-year observations and excludes dividend yield in stock return measurement. This study provides recent evidence from Indonesian LQ45 firms by highlighting the role of growth and cash flow signals in explaining stock returns.